(untitled) (Proceedings of the International Conference on Future of Education, 2018)
This paper outlines the characteristics of MOOCs (Masive Open Online Courses) and their development and tendencies that seem to indicate a process of dehumanization. This could be considered the basis of problems that this teaching modality is demonstrating. Firstly with the achievement of their stated objective of being a solution to the problem of mass training for life, as the potential beneficiaries of MOOCs are abandoning this type of course massively. Taking this point as the background issue, the central objective of this paper is to research a group of factors which, in the opinion of the authors, contribute to the humanizing of MOOCs, and to infer from them principles which it is considered must be applied to support a humanizing methodology to be developed, one which in turn motivates and helps the students in their purpose to achieve the training and knowledge they need to survive in this and a future knowledge based society.